Potency of Garcinia mangostana L peel extract combined with demineralized freeze-dried bovine bone xenograft on IL-1β expression, osteoblasts, and osteoclasts in alveolar bone - Imam Safari Azhar; Utari Kresnoadi; Retno Pudji Rahayu (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Alveolar bone plays an important role in supporting dentures. One socket preservation procedure is the application of bone graft to the tooth socket immediately after extraction. The administration of Garcinia mangostana L peel extract combined with demineralized freeze-dried bovine bone xenograft (DFDBBX) is assumed to decrease the number of osteoclast cells and IL-1β expressions, while also increasing that of osteoblast cells. Purpose: This study aimed to establish the potency of Garcinia mangostana L peel extract combined with DFDBBX on interleukin 1β expressions, osteoclast cells, and osteoblast cells during the preservation of tooth extraction sockets. Methods: This research constituted experimental laboratory-based research using 56 Cavia cobayas as specimens with randomized factorial design (true experimental design). These subjects were divided into eight groups, given PEG, DFDBBX, mangosteen peel extract or a combination of mangosteen peel extract and DFDBBX, and subsequently anesthesized before their left mandibular incisors were extracted. Thereafter, the post-extraction sockets were treated with PEG, DFDBBX, mangosteen peel extract or a combination of mangosteen peel extract and DFDBBX. The sockets were examined by means of HE and immunohistochemical staining on days 7 and 30 after extraction. The data obtained was analyzed with a one-way ANOVA test. Results: The results of the one-way ANOVA test showed that the average number of osteoblasts, osteoclasts, and IL-1β expressions varied significantly between the groups. Conclusion: The combination of mangosteen peel extract and DFDBBX can potentially increase osteoblasts, while also decreasing osteoclasts and IL-1β expressions in the alveolar bones of Cavia cobaya.